2018
DOI: 10.1002/2017wr021290
|View full text |Cite
|
Sign up to set email alerts
|

Next‐Generation Intensity‐Duration‐Frequency Curves for Hydrologic Design in Snow‐Dominated Environments

Abstract: There is a renewed focus on the design of infrastructure resilient to extreme hydrometeorological events. While precipitation‐based intensity‐duration‐frequency (IDF) curves are commonly used as part of infrastructure design, a large percentage of peak runoff events in snow‐dominated regions are caused by snowmelt, particularly during rain‐on‐snow (ROS) events. In these regions, precipitation‐based IDF curves may lead to substantial overestimation/underestimation of design basis events and subsequent overdesig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 70 publications
1
107
1
Order By: Relevance
“…Berghuijs et al () explored the dominant flood‐generating mechanisms across the continental United States and found that snowmelt and ROS events were more robust predictors of the flooding response than rainfall over the western United States. This is further confirmed by Yan et al (), Yan, Sun, Wigmosta, Skaggs, Leung, et al () who found that the standard precipitation‐based intensity‐duration‐frequency curves often significantly underestimate extreme events in snow‐dominated environments, suggesting a critical role of snow in flooding in those environments. With a warming climate, ROS‐driven flood risk is projected to increase significantly in many western United States river basins with more frequent ROS events at high elevations where seasonal snowpack persists even in a warmer climate (Musselman et al, ).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Berghuijs et al () explored the dominant flood‐generating mechanisms across the continental United States and found that snowmelt and ROS events were more robust predictors of the flooding response than rainfall over the western United States. This is further confirmed by Yan et al (), Yan, Sun, Wigmosta, Skaggs, Leung, et al () who found that the standard precipitation‐based intensity‐duration‐frequency curves often significantly underestimate extreme events in snow‐dominated environments, suggesting a critical role of snow in flooding in those environments. With a warming climate, ROS‐driven flood risk is projected to increase significantly in many western United States river basins with more frequent ROS events at high elevations where seasonal snowpack persists even in a warmer climate (Musselman et al, ).…”
Section: Introductionsupporting
confidence: 65%
“…We acquired SWE measurements and meteorological records consisting of daily minimum/maximum air temperature and daily total precipitation from 785 active National Resource Conservation Service SNOTEL stations across the western United States, all operated by the U.S. Department of Agriculture Natural Resources Conservation Service. All data from the 785 SNOTEL stations were first screened using the quality assurance and quality control procedures that were initially developed by Serreze et al () and later enhanced by Yan et al (). To develop regional parameters and evaluate the spatial variation of model skill, we selected 246 SNOTEL stations with the longest common period of reliable records from Water Years (WYs) 2007 through 2013.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More evaluation of the simulated precipitation is also described in Chen et al (). The simulated snowpack is evaluated using snow water equivalent from the Snow Telemetry (SNOTEL) stations (Yan et al, ) during the water years of 2006–2013. The SNOTEL data set has been quality controlled, and water years 2006–2013 are chosen to provide a continuous data record.…”
Section: Methodsmentioning
confidence: 99%
“…Although the aforementioned studies provide significant findings about how the mountain snowpack is changing under a warming climate, none of these studies has explicitly examined the changes in specific mechanisms that provide water at the land surface available to generate runoff ( W ). The W ‐generating mechanisms can be classified as rainfall on snow‐free ground, snowmelt only, and rain‐on‐snow (ROS; Yan et al, ). Understanding the changes in different W ‐generating mechanisms has direct implications for water resources management, because rainfall mechanism alone poorly explains the spatial and temporal variabilities of flood risk across the western United States (Berghuijs et al, ).…”
Section: Introductionmentioning
confidence: 99%